Editorial Board (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
Editors:Ruud DuvekotSusan ForseilleAlan MandellNan TraversGuest Editors:Deirdre GogginMartina NeedhamAssociate Editor:Carl BurkartSpecial Issue Editorial Team Members:Alexa CollesidesJoshua Nelson